The pursuit of intimacy: intimate relationship development for women with physical disabilities - Ruiz, Derek; Kriofske Mainella, Alexandra; Rosenthal, David A. (Frontiers in Rehabilitation Sciences, 2023)
As people age, intimate relationships, both sexual and non-sexual, are essential contributors to overall quality of life for people with and without disabilities. Research indicates that some people with disabilities encounter obstacles in developing relationships and exploring and expressing intimacy. The research available on intimate relationship development focuses on people without disabilities; however, since people with disabilities face unique challenges in developing such relationships, it is crucial to better understand these difficulties to potentially address them. This consensual qualitative research aims to add to the overall knowledge regarding the research questions: What are the overall subjective experiences of women with visible physical disabilities in developing intimate relationships, and what aspects of intimacy and sexuality are most important to these women. Physical disabilities were chosen as a focus to control for different experiences based on disability type. Those interviewed identified aspects of intimacy and sexuality most important to intimate relationship development. This project's larger scope was to better understand barriers and facilitators to intimate relationship development; those identified were linked to practical applications for future consideration.